''Proteomineering'': has the mine been excavated?. (August 2011) - Panfoli, Isabella; Bruschi, Maurizio; Ravera, Silvia; Candiano, Giovanni
Evaluation of: Di Girolamo F, Boschetti E, Chung MC, Guadagni F, Righetti PG. ''Proteomineering'' or not? The debate on biomarker discovery in sera continues. J. Proteomics 74(5), 589––594 (2011). The combinatorial peptide ligand library in association with mass spectrometry can greatly enhance the dynamic range of the analysis of low- and very low-abundance proteins constituting the vast majority of species in any sample. When compared with untreated samples, the increment in detection of low-abundance species appears to be at least fourfold. Recently, the combinatorial peptide ligand library has been challenged; however, it has been clearly demonstrated in the evaluated paper that the protocols for elution of the captured polypeptides make the difference. Therefore, the solid-phase ligand library made of hexapeptides remains a promising and unique tool for biomarker discovery.